The Artistic Image in the Works of Jamil Haidar and Mustafa Jamal al-Din: A Comparative Study with The Remembrance of al-Husayn as a Model - الظفيري إنعام حسن شمران (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This study explores the artistic imagery in the poetry of Jamil Haidar and Mustafa Jamal al-Din through a comparative analysis of their poems on the remembrance of Imam al-Husayn. The image is considered a fundamental tool for reshaping the emotional and cultural consciousness associated with this remembrance. The research analyzes the structure and formation of imagery، highlighting stylistic and semantic differences between the two poets: Jamal al-Din tends toward a cohesive، contemplative traditionalism، while Haidar employs modernist techniques characterized by condensation and deviation to produce tension-filled images. The study affirms that the remembrance of al-Husayn is not merely a historical event but a symbol embodying major values such as sacrifice، justice، and rebellion. Thus، the artistic image becomes a space for merging individual experience within a collective horizon، balancing the sensory and the transcendent، making poetry a vision and interpretation that transcends direct expression. The research offers a renewed reading of religious poetry as a dynamic artistic discourse open to reinterpretation and renewal.